2022
DOI: 10.1111/jocd.14926
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy for hair removal in dark skin types III and IV with a high‐powered, combined wavelength (810, 940 and 1060 nm) diode laser: A single‐site pilot study

Abstract: Background: Previous studies have demonstrated the superior efficacy of a highpower diode laser (4800 W) with a wavelength of 810 nm over others with less power and the same wavelength, while also being safe and comfortable for the patient.However, the use of this laser is limited on dark skin.Objectives: This study aims to compare the efficacy, safety, and comfort of a 4800 W diode laser (810 nm) with that of the new Blend diode laser (810 nm, 940 nm, and 1064 nm). Furthermore, the study aims to demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
(11 reference statements)
1
9
0
Order By: Relevance
“…These results are consistent with those presented in the studies by Fajardo et al [13] and Gold et al [15] where the Primelase device with the triple-wavelength diode laser showed greater reduction than the 810 nm diode laser by 55% and 12%, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with those presented in the studies by Fajardo et al [13] and Gold et al [15] where the Primelase device with the triple-wavelength diode laser showed greater reduction than the 810 nm diode laser by 55% and 12%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Results have been published with the combination of 755, 810 and 1064 nm [12]. In other studies, triple wavelengths of 810, 940 and 1064 nm have been used [13] [14] [15]. However, we have not found any study using triple wavelengths on Indian patients.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…16 In other studies, different combinations of wavelengths have been used, such as 810, 940, and 1060 nm. 5,17,18 The main advantage of this combination is that longer wavelengths (810 and 940 nm compared with 755 and 810 nm) are less affected by scattering in the dermis, allowing for deeper penetration which uniformly heats the hair, thereby increasing the safety of the procedure even at high laser fluences since there is less absorption by melanin and less epidermal heating and burns. Additionally, the 940 and 1060 nm wavelengths are significantly absorbed by water and blood, which contributes to the heating of the hair follicle in combination with the absorption by melanin in the hair.…”
Section: Introductionmentioning
confidence: 99%
“…There are three common wavelengths in commercial use, corresponding to the three types of lasers on the market including; 755 nm alexandrite lasers, 810 nm diode lasers, and 1064 nm Neodymium-doped Yttrium Aluminum Garnet (Nd:YAG) lasers [11,12] .…”
Section: Introductionmentioning
confidence: 99%